The OS Faces a Brave New World. - Geer, David (Computer (00189162), 2009)
The article focuses on major software-related developments that are minimizing the reliance of software on specific, full-featured server and personal computing (PC) operating systems (OS). It describes how cloud computing, virtualization and application-development frameworks affect the components, responsibilities, roles, installation and applications of OS. The development of OS since the 1950s and the factors that made the choice and use of an OS important are also discussed.